CTNI-21. PHASE 2 STUDY OF VAL-083 AND RADIOTHERAPY IN NEWLY DIAGNOSED MGMT-UNMETHYLATED GBM. (12th November 2021) - Chen, Zhong-ping; Guo, Cheng-Cheng; Qun-ying, Yang; Li, Jia-Wei; Wu, Shao-xiong; Bacha, Jeffrey; Johnson, Gregory; Langlands, John; Kwan, Claire; Kanekal, Sarath; Schwartz, Richard; Steino, Anne; et al.
Abstract: Approximately 60% of glioblastoma multiforme (GBM) patients possess an unmethylated methylguanine DNA-methyltransferase (MGMT) gene promoter, which confers a limited clinical response to standard-of-care treatment with temozolomide (TMZ), resulting in shorter median survival when compared to patients with a methylated MGMT promoter. VAL-083 is a novel bi-functional DNA targeting agent that induces interstrand DNA cross-links at N 7 -guanine, leading to DNA double-strand breaks and ultimately cell death. VAL-083 circumvents MGMT-mediated TMZ resistance in vitro and in vivo . A Phase 2 study has been conducted to evaluate efficacy and safety of VAL-083 when administered concurrently with radiation therapy (RT) in newly diagnosed MGMT unmethylated GBM. The study was conducted in 2 stages: Stage 1 was a dose-escalation phase to confirm the dose of VAL-083 in this setting. Patients received VAL-083 at 20, 30, or 40 mg/m 2 /day x 3 days every 21 days along with standard radiation treatment (RT) (2 Gy/day, 5 days/week for 6 weeks). At the end of this stage, 30 mg/m 2 /day of VAL-083 in combination with RT was generally safe and well-tolerated. Stage 2 was an expansion phase to enroll up to 20 additional patients at the 30 mg/m 2 /day of VAL-083 in combination with RT. All patients have been enrolled, with a total of 29 patients in the study, and 25 patients receiving 30 mg/m 2 /day VAL-083. All 29 patients have completed treatment and patients are in the follow-up phase of the study. Consistent with our prior experience, myelosuppression was the most common adverse event. As of March 2021, 22/29 (75.9%) subjects had disease progression. The median progression free survival for all patients enrolled was 9.3 (95%CI: 6.4-12.0) months. Sixteen (16/29; 55.2%) patients had died, and median overall survival for all patients enrolled was 19.6 (95%CI: 14.0-22.4) months. Further safety and efficacy updates will be presented at the meeting. Clinicaltrials.gov identifier: NCT03050736.